KOMUNIKASI INTERPERSONAL GURU SEKOLAH MENENGAH KEJURUAN NEGERI 3 PADANG - FADHILA HAMIDATUS SHIFAH (Jurnal Bahana Manajemen Pendidikan, 2018)
The purpose of this research is to know the information about teacher interpersonal communication. Because the hind of research is population research, the researcher takes 56 teachers  as the population and he sample. The instrument of this research uses questioner that it uses likert scale which has been tasted that validity and realibility. Futhermore, the researcher uses mean for data analyzing. The results of this research indicates that teacher interpersonal communication in SMKN 3 Padang, can be put on sufficiency of categorization.  Keywords: Interpersonal Communication